2023
DOI: 10.1155/2023/4602148
|View full text |Cite
|
Sign up to set email alerts
|

Ground-Air Traffic Congestion Propagation Model Based on Hierarchical Control Interdependent Network

Abstract: A multilayer network approach to model and analyze air traffic networks is proposed. These networks are viewed as complex systems with interactions between airports, airspaces, procedures, and air traffic flows (ATFs). A topology-based airport-airspace network and a flight trajectory network are developed to represent critical physical and operational characteristics. A multilayer traffic flow network and an interrelated traffic congestion propagation network are also formulated to represent the ATF connection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…However, the operation of these airport clusters, which are also known as "airport metroplex", is coupled and complex, largely due to their co-location within the same terminal area airspace [1][2][3]. The mutual influence among these airports and their shared use of airspace resources inevitably lead to lower operational efficiency [4][5][6][7].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…However, the operation of these airport clusters, which are also known as "airport metroplex", is coupled and complex, largely due to their co-location within the same terminal area airspace [1][2][3]. The mutual influence among these airports and their shared use of airspace resources inevitably lead to lower operational efficiency [4][5][6][7].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…This information is invaluable for designing targeted interventions, implementing travel restrictions, and optimizing screening measures at airports. Jiang et al (2023), as well as Pastor-Satorras and Vespignani (2002), identified the SIS model when applied to air traffic networks that allow individuals to transition between susceptible and infectious states multiple times, reflecting the continuous exposure and recovery patterns observed in real-world scenarios. This model enables the investigation of the potential for recurrent outbreaks within air travel networks.…”
Section: Introductionmentioning
confidence: 99%